2017
DOI: 10.18632/oncotarget.21360
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of XRCC4 expression in hepatocellular carcinoma

Abstract: BackgroundOur previous investigations have shown that the variants of X-ray repair complementing 4 (XRCC4) may be involved in hepatocellular carcinoma (hepatocarcinoma) tumorigenesis. This study aimed to investigate the possible prognostic significance of XRCC4 expression for hepatocarcinoma patients and possible value for the selection of transarterial chemoembolization (TACE) treatment.Materials and MethodsWe conducted a hospital-based retrospective analysis (including 421 hepatocarcinoma cases) to analyze t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 41 publications
3
22
0
Order By: Relevance
“…However, many studies have suggested that pa‐TACE displays different therapeutic effects on hepatocellular carcinoma with different genetic profiles. For example, different genetic features such as different expression of polycomb chromobox 4 and x‐ray repair complementing 4 among individuals with hepatocellular carcinoma have been proven to modify MVD, and ultimately lead to unsuccessful pa‐TACE treatment . Genetic changes in a disintegrin and metalloproteinase with thrombospondin motifs 5, microRNA‐1268a, microRNA‐196a, and microRNA‐499a may change individual's response to pa‐TACE treatment and result in treatment failure …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, many studies have suggested that pa‐TACE displays different therapeutic effects on hepatocellular carcinoma with different genetic profiles. For example, different genetic features such as different expression of polycomb chromobox 4 and x‐ray repair complementing 4 among individuals with hepatocellular carcinoma have been proven to modify MVD, and ultimately lead to unsuccessful pa‐TACE treatment . Genetic changes in a disintegrin and metalloproteinase with thrombospondin motifs 5, microRNA‐1268a, microRNA‐196a, and microRNA‐499a may change individual's response to pa‐TACE treatment and result in treatment failure …”
Section: Discussionmentioning
confidence: 99%
“…For example, different genetic features such as different expression of polycomb chromobox 4 and x-ray repair complementing 4 among individuals with hepatocellular carcinoma have been proven to modify MVD, and ultimately lead to unsuccessful pa-TACE treatment. (30,32) Genetic changes in a disintegrin and metalloproteinase with thrombospondin motifs 5, microRNA-1268a, microRNA-196a, and microRNA-499a may change individual's response to pa-TACE treatment and result in treatment failure. (15,31) In this study, we are particularly concerned with the association between microRNA-4651 expression in cancerous tissues and pa-TACE treatment, primarily because our previous reports showed a higher serum mciroRNA-4651 level among patients with aflatoxin B1-related hepatocellular carcinoma, and this upregulation significantly correlated with tumor angiogenesis and prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past decades, growing reports have exhibited that the abnormal structures and functions of XRCC4 may alter the capacity of DNA repair and ultimately result in human diseases [17][18][19][20][21][22]. Several recent studies have also shown that the genetic alterations in the coding regions of XRCC4 can modify hepatocellular carcinoma (HCC) risk and prognosis [23][24][25][26][27]. However, the effects of this genetic alteration on the hepatic toxicity of AFB1 is unclear.…”
Section: Introductionmentioning
confidence: 99%